Impact of Heartfulness meditation practice on anxiety, perceived stress, well-being, and telomere length - Thakur, Mansee; Patil, Yogesh; Philip, Sanjana T.; Hamdule, Tahreem; Thimmapuram, Jayaram; Vyas, Nishant; Thakur, Kapil (Frontiers in Psychology, 2023)
Objective Exhaustion, stress, and burnout have all been found to be reduced using techniques like yoga and meditation. This study was carried out to check the effectiveness of Heartfulness practice (a form of meditation) on certain psychological and genetic variables. Methods A total of 100 healthy individuals (aged 18–24) were recruited and randomized into two groups-Heartfulness intervention and control group. The intervention was carried out for 03 months. Participants from both groups were analysed for their cortisol levels and telomere length before and after the intervention. Psychometric measures of anxiety, perceived stress, well-being and mindfulness were carried out using Beck Anxiety Inventory (BAI), Perceived Stress Scale (PSS), WHO-Well-being Index (WHO-WBI) and Five Facet Mindfulness Questionnaire (FFMQ). Results The cortisol levels in the meditators group significantly decreased (p < 0.001) after the intervention as compared to the non-meditators group, whereas, the telomere length increased in the mediators group. This increase was not significant (p > 0.05). Anxiety and perceived stress also decreased post intervention, and well-being as well as mindfulness increased, as assessed by the questionnaire tools, although the decrease in perceived stress was statistically insignificant (p > 0.05). A negative correlation was observed between telomere length and cortisol (stress biomarker), whereas a positive correlation was found between telomere length and well-being. Conclusion Our data provide evidence that Heartfulness meditation practice can improve our mental health. Additionally, telomere length is shown to be affected by cortisol levels, and this meditation practice can also help to increase telomere length, and thereby slow down cellular aging. However, future studies with larger sample size are required to confirm our observations.